Pesan Moral Dalam Film “SEJUTA SAYANG UNTUKNYA” Karya Herwin Novianto - Faisal Dias Rekananda, Anita Agustina Wulandari (DIGICOM : Jurnal Komunikasi dan Media, 2022)
Film means a series of still images that when displayed on a screen create the illusion of a moving picture. Movies are entertainment for all walks of life these days. One of the end 2020 Indonesian family drama movies is A Million Loves for Him movie directed by Herwin Novianto. This film addresses the correlation between fathers and daughters and idealistic and realistic things that need to be balanced. This study uses a semiotic analysis approach by Charles Sanders Piercen that uses the dimensions of icons, indices and symbols as mapping for viewing the film Sejuta Sayang Untuknya. Semiotic analysis is usually applied to visual images or text. In this method, the functioning of images is questioned by relating them to ideological structures that organize meaning. Furthermore, this study uses a qualitative method with a narrative approach using a critical thinking framework. In addition, through the analysis of the film message, residents can grasp the messages contained in Indonesian films, especially the discourse on the confrontation of fathers and daughters, which are presented with moral means according to the original requirements in everyday life, messages expressed in the form of honesty, respect , responsibility and feeling are raised, with the example of Charles Sanders Pierce's theory being shown through cues (representatives) manifesting through an object, which can lead the audience to interpret the meaning of the origin of the film.